Preparation and purification of Flavobacterium heparinum chondroitinases AC and B by hydrophobic interaction chromatography - Aguiar,J.A.K. (1999)
Flavobacterium heparinum is a soil bacterium that produces several mucopolysaccharidases such as heparinase, heparitinases I and II, and chondroitinases AC, B, C and ABC. The purpose of the present study was to optimize the preparation of F. heparinum chondroitinases, which are very useful tools for the identification and structural characterization of chondroitin and dermatan sulfates. We observed that during the routine procedure for cell disruption (ultrasound, 100 kHz, 5 min) some of the chondroitinase B activity was lost. Using milder conditions (2 min), most of the chondroitinase B and AC protein was solubilized and the enzyme activities were preserved. Tryptic soy broth without glucose was the best culture medium both for bacterial growth and enzyme induction. Chondroitinases AC and B were separated from each other and also from glucuronidases and sulfatases by hydrophobic interaction chromatography on HP Phenyl-Sepharose. A rapid method for screening of the column fractions was also developed based on the metachromatic shift of the color of dimethylmethylene blue.